Pengaruh Laminasi Silang Dengan Perekat Epoxy Pada Kayu Palaka Terhadap Nilai Kuat Lentur Kayu: Effect of Cross Lamination with Epoxy Adhesive on Palaka Wood on the Flexural Strength of Wood - Fajar, Muhammad Nur; Purwantoro, Didik Setya; Arifin, Herlina; Maysyurah, Alfina; Aris, Mohammad (Universitas Negeri Surabaya, 2024)
Indonesia is one of the countries with abundant timber resources The huge demand for timber has an impact on the availability of timber which is decreasing every year due to large-scale exploitation. So it is necessary to carry out innovations or wood management technology to overcome these problems, one of the technologies that can be used is laminated wood. In this study, a test of bending strength will be carried out on wood without lamination process and wood with a cross-lamination process using epoxy. This test was carried out to see the effect of the use of cross lamination on wood, and the type of wood used was Palaka wood. From the results of this study, it can be seen that the bending strength value of palaka wood without lamination is 28.60 MPa, while palaka wood cross-laminated with epoxy adhesive has a bending strength value of 16.06 MPa. The amount of decrease in bending strength that occurs after cross-laminating with epoxy is 43.84% for palaka wood without lamination process.